Digoxin specific antibody fragments (Digibind) in digoxin toxicity. (3rd September 2009) - Ip, Dorothy; Syed, Hafiz; Cohen, Maurice
Abstract : Digoxin levels may be falsely raised after administration of digoxin specific antibody fragments